Vulnerability and Survival Strategy by Food Street Vendors: Case Study in Triangle Gold of DKI Jakarta - Dicky Rachmawan; Muhammad Luthfi; Rusydan Fathy (JSW (Jurnal Sosiologi Walisongo), 2021)
Street vendor (Pedagang Kaki Lima - PKL) is the most incarnation of the informal economy with the biggest role even at the state level. Unfortunately, PKL is blamed as the source of problems and is surrounded by the threat of eviction, which still happened in DKI Jakarta, as the symbol and magnet of development in Indonesia. This study aims to reveal the vulnerability of the PKL in the Golden Triangle of Jakarta and the defensive strategies they carry out. The qualitative method with a case study strengthened by life history for revealing the vulnerability and survival strategy of the PKL household is applied in this study. The result shows the unforeseeable fact that PKL in Triangle Gold of DKI Jakarta potentially can reach an income as same as the regional minimum wage in DKI Jakarta. At the same time, the eviction and number of customers are the PKL’s vulnerability factors. Social capital is essential to start a new job or business as PKL, while strengthened by push and pulling factors to migrate from rural to city. Bridging and bonding with stakeholders through adaptation to the changing rule are the PKL’s main strategies to survive; besides, preserving the identity and norms of PKL boosts the PKL community's adhesion to encounter hard times. Beyond that, resignation value to God and effort for growing are determinant aspects that differ between PKL who have more or less revenue.